Implementation of the Independent Curriculum Policy at An Nizam Medan Private Middle School - Ar Rahma Pasaribu, Nopi Yanti; Simbolon, Nur Anisa; Br Tarigan, Putri Juliani; Uli Sembiring, Vanessa; Rifai, Muhammad; Ivanna, Julia (JUPE : Jurnal Pendidikan Mandala, 2024)
This study aims to review the implementation of the curriculum policy of Independent Learning in private Junior High School an Nizam Medan to achieve the goal of curriculum competence independent learning in order to create a superior generation. The research method used is a qualitative approach. In this study, data collection techniques were conducted through observation, interviews and documentation. The Merdeka curriculum focuses on creative and free thinking. The Ministry of Education and culture has introduced the Driving School Program as one of the programs to encourage the implementation of an independent curriculum in every school. The results obtained are (1) Private Junior High School an Nizam Medan has successfully implemented an independent curriculum. (2) there are strategies that support the successful implementation of the independent curriculum in private Junior High School a Nizam Medan, (3) the challenges faced in the implementation of the independent curriculum.